The concept of employer’s insolvency in the act on the protection of employee claims in the event of employer’s insolvency - Liskowski, Mariusz (Studia Iuridica Toruniensia, 2019)
This article analyses selected scenarios linked to the concept of employer’s insolvency by the Act of 13 July 2006 on the protection of employee claims in the event of employer’s insolvency. The author takes on the subject title by referring primarily to the protective function and pointing to difficulties in interpreting the provisions of the said Act associated with the concept of insolvency. The analysis leads to a conclusion that according to the Act the employer’s insolvency does not necessarily mean that the employer has no funds to pay the amounts due to employees. The reports of the Chief Labour Inspector on the operations of the National Labour Inspectorate lead one to a conclusion that the protection provided under the Act is not sufficient. The author advocates adopting new solutions under the Act, with a view to future law.